Incorporating GPT in a Term Project in Advanced Accounting: An Exploration in AI-Assisted Research - Han, Lei (Journal of Applied Business and Economics, 2024)
This study modifies an existing term project to afford an GPT-assisted research opportunity for advanced accounting students. Most students surveyed agreed that the project helped them gain working knowledge on GPT, felt more confident in using GPT, and were open to the idea of using GPT in varied settings. However, many students claimed that they would not fully rely on GPT to do their work. A similar approach can be easily adopted to modify traditional essay assessments in other courses or disciplines to familiarize students with generative artificial intelligence's capabilities.